Vocabulary Building sebagai Modal Dasar Keahlian Berbahasa Inggris pada Peserta Didik Asrama Yatim Keluarga Muslim The Castilla - Iswanto, Ary; Mulyati, Sri; Yastanti, Unpris; Vidada, Irwin Ananta (Jurnal Abdimas Komunikasi dan Bahasa, 2021)
English language skills have 4 (four) main skills, including speaking, listening, reading, and writing. These skills must be owned by someone who wants to master the language, especially English. Building vocabulary or learning English vocabulary is the beginning of the expertise of all these skills. Pronounce and write vocabulary techniques properly and correctly can affect the speed of the English-speaking process. The English Literature Study Program Team as a resource and tutor who conducts Community Service for the students of The Castilla Muslim Orphanage Dormitory through vocabulary building training with collaborative learning methods. This method is used as an effort to facilitate participants and tutors in providing vocabulary training where face-to-face is still prohibited. From the Community Service activities, significant results were obtained through the pre-test and post-test on the participants. Then there is a C value of 35% and D as much as 45% in the pre-test. Meanwhile, the value of C is 15% and the value of D is 10%.